Advances in adjuvant therapy of biliary tract cancer: an overview of current clinical evidence based on phase II and III trials. (July 2020) - Belkouz, A.; Wilmink, J.W.; Haj Mohammad, N.; Hagendoorn, J.; de Vos-Geelen, J.; Dejong, C.H.C.; Homs, M.Y.V.; Groot Koerkamp, B.; van Gulik, T.M.; van Oijen, M.G.H.; Punt, C.J.A.; Klümpen, H.
Abstract: Patients with biliary tract cancer (BTC) have a high recurrence rate after complete surgical resection. To reduce the risk of recurrence and to improve survival, several chemotherapeutic agents that have shown to be active in locally advanced and metastatic BTC have been investigated in the adjuvant setting in prospective clinical trials. Based on the results of the BILCAP phase III trial, capecitabine was adapted as the standard of care by the ASCO clinical practice guideline. Ongoing randomized controlled trials mainly compare capecitabine with gemcitabine-based chemotherapy or chemoradiotherapy. This review provides an update of adjuvant therapy in BTC based on published data of phase II and III trials and ongoing randomized controlled trials (RCTs).